IMAN SEBAGAI BASIS PENDIDIKAN KARAKTER - Haryanto, Sri; Faizal, Vava Imam Agus (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2022)
The purpose of this study is to describe faith as the basis for character education. As qualitative research with a library model, the research data is in the form of character education literature which is accessed through e-journals and books. The data collection technique is done by documentation. The researcher documents the character education literature from the sources mentioned hereinafter for analysis. The data analysis was carried out by data reduction, data presentation, and concluding. At the data analysis stage, the researcher reduced character education literature which was then presented systematically. The final stage is the researcher concludes the critical analysis. The results of the study state that faith is the main theological foundation, while sharia and morals (character) will be the implementation of believers in living life. Because faith will give birth to a high commitment. With this commitment, it gives birth to values ​​which in turn give birth to the character in the form of action. The action in question can influence the pronunciation of the tongue and the formation of human attitudes, morals, character, mindset, and forms of worship. Such actions can even have an impact on the surrounding environment.